A Meta-Analysis of the Effectiveness of Cognitive-Behavioural Therapies for Late-Life Depression - Thomas, William J.; Hauson, Alexander O.; Lambert, Jessica E.; Stern, Mark J.; Gamboa, Julia M.; Allen, Kenneth E.; Stephan, Rick A.; Kimmel, Christine L.; Wollman, Scott C.; Hall, Matthew G.; Towns, Benjamin L.; Sari, Celina; et al. (Canadian Journal of Counselling and Psychotherapy, 2018)
A comprehensive meta-analysis was conducted using studies of cognitive-behavioural-therapy based interventions (CBT-BIs) for late-life depression. Patient characteristics, CBT modality, and other study variables were analyzed using subgroup and metaregression analysis methods. Results showed the collective treatment effect of CBT-BIs for reducing late-life depression to be moderate (g = -0.63) with significant heterogeneity (I2 = 66.12%). CBT-BIs were found to be no more effective immediately posttreatment than other psychological treatments, pharmacotherapy, or combination interventions. The data support the notion that CBT is more effective in the long term.